EMPLOYEE ENGAGEMENT MEDIATES THE ACHIEVEMENT MOTIVATION AND ORGANIZATIONAL CULTURE TOWARDS TEACHER PERFORMANCE AT BINA INSAN MANDIRI SCHOOL, JAKARTA - Ira Sumiati; Singmin Johanes Lo (Dinasti Publisher, 2022)
This research purposes to explore the role of achievement motivation and organizational culture that affected employee engagement in teacher performance. The research population here was permanent teachers at Bina Insan Mandiri School that is located in DKI Jakarta, with a total sample of 65 teachers. The data analysis method used the Structural Equation Model-Partial Least Square (SEM-PLS). The result indicates that achievement motivation and organizational culture have a positive and significant impact on teacher performance and employee engagement, likewise to employee engagement which has positive and significant in mediates the effect of achievement motivation and organizational culture on performance.